Utilization of Maizena Flour as a Basic Material for Making Bioplastics - Ruhendi, Raditya Adinaka; Fauzi, Siska (LAVOISIER: Chemistry Education Journal, 2023)
Plastic is a widely used packaging material, but has a negative impact on the environment because it is difficult to decompose in nature. Many experts have developed technologies for the production of biodegradable plastics orbioplastics made from natural and environmentally friendly materials. Starch-based biodegradable plastics are easier to produce and access to raw materials is easier to obtain. So in this research an experiment was carried out using cornstarch as a base ingredient for making bioplastics. Examined with quantitative methods through experiments obtained results of comparisons of differences in water concentrations and differences in glycerin concentrations.Then a mechanical test was carried out to see the ability to decompose bioplastics with water. After conducting research on the use of bioplastics from cornstarch as asubstitute for plastic, it can be concluded that the best bioplastic produced is at a Glycerin Concentration of 5 mL and a Water Concentration of 100 ml.